The Multifaceted Role of Th1, Th9, and Th17 Cells in Immune Checkpoint Inhibition Therapy - Lee, Jongdae; Lozano-Ruiz, Beatriz; Yang, Fengyuan Mandy; Fan, Dengxia Denise; Shen, Liya; González-Navajas, Jose M. (Frontiers in Immunology, 2021)
During the last decade, immune checkpoint inhibition (ICI) has become a pillar of cancer therapy. Antibodies targeting CTLA4 or PD-1/PD-L1 have been approved in several malignancies, with thousands of clinical trials currently underway. While the majority of cancer immunotherapies have traditionally focused on enhancing cytotoxic responses by CD8+ or NK cells, there are clear evidences that CD4+ T cell responses can modulate the immune response against tumors and influence the efficacy of ICI therapy. CD4+ T cells can differentiate into several subsets of helper T cells (Th) or regulatory T cells (Treg), with a wide range of effector and/or regulatory functions. Importantly, different Th subsets may have different and sometimes contrasting roles in the clinical response to ICI therapy, which in addition may vary depending on the organ and tumor niche. In this review, we discuss recent evidence that highlights how ICI therapy impacts Th cells and vice versa. These data might be important designing better interventions that unleash the full potential of immune response against cancer.